Insaniah (humanistic) economics of waqf: From IR 4.0 to a human-centered tawhidic society 5.0 - Mohd Isa, Mohd Yaziz Bin; Mohamed, Zulkifflee Bin (European Journal of Islamic Finance, 2020)
This paper provides an account of the commonalities of theoretical foundations of insaniah (humanistic) economics that is prevailing in transactions of waqf (an Islamic endowment). The paper establishes the integration of the two theoretical foundations, the insaniah (humanistic) economics in the waqf transactions. Taking into accounts waqf is about preserving the usufruct (the right-of-use) of specified asset(s) by donor (waqif) so that it may benefit the society in the long run (AAOIFI, 2018), and conceptually ownership of a waqf belongs to Allah S.W.T., alone; the paper proposes a trajectory from an existing secular economics of societal transformation society 5.0 (a super smart society). The society 5.0 itself is a societal transformation plan from IR 4.0 and emphasizes on social implications, ethics and social acceptance by all stakeholders. In view of the substantial role of waqf as one of Islamic economic rites, a human-centred tawhidic society 5.0 is the common purpose in all the transformational phases. In the society 5.0, movements toward incorporating new elements from both secular and Islamic economics into existing technologies and knowledge, thereafter, designing and creating previously unknown business services are gaining visibility. Taking into accounts the scope of waqf transactions has expanded concurrently on the verge of the human-centered society 5.0 from traditional platforms due to the socio-economic demands, it becomes increasingly necessary the human-centered tawhidic-based principles is the foundation for economic activities for the ummah. Innovation is increasingly important as a driving force for economy activities, without a doubt. Underneath all this is “digitized information”, in the future, innovative information-based technologies such as Internet of Things (IOT), artificial intelligence (AI), and robotics are expected to generate new added value.